Managing and Monitoring Grand Design Public Administration Reforms - Verheijen, Tony (World Bank, Washington, DC, 2016)
A grand design attempt at public administration reform can be thought of as any centrally designed, multiple agency reform program or process designed to modernize or improve the performance of administrative structures at the center of Government, usually with a focus on addressing persistent underlying inefficiencies. International practice shows that reforming selected central institutions (especially those that hold the purse strings) is a different matter altogether from addressing performance issues in large ministries with a service delivery mandate. Therefore, it is of critical importance to ‘unpack’ these particular reforms and uncover the persistent issues that arise in countries attempting to pursue such reforms. The four grand design cases highlighted here were selected for their comparability in terms of size and economy, and as examples of reforms from different regions. The cases presented here are Brazil, Nigeria, Russia and Tanzania. Each of these cases has specific characteristics, based on a unique country or reform context, but they share the features of a broad, across-the-board reform approach (in three of the four cases with a clear sub-national dimension that is distinct from the national one). This note focuses on the three critical design aspects of such reforms: a) reform coherence, b) effective anchorage and, c) blending technocratic solutions with substantive service delivery improvements.